Comparison of serum levels of IL-6, IL-8, TGF-Î² and TNF-Î± in coronary artery diseases, stable angina and participants with normal coronary artery - Sepehri, Zahra Sepehri; Masoomi, Mohammad; Ruzbehi, Fatemeh; Kiani, Zohreh; Nasiri, Ali Akbar; Kohan, Farhad; Sheikh Fathollahi, Mahmood; Kazemi Arababadi, Mohammad; Kennedy, Derek; Asadikaram, Gholamreza Asadikaram (Cellular and Molecular Biology, 2018)
Cytokines, which typically regulate the immune responses, play a role in cardiovascular diseases such as coronary artery diseases (CAD) and ischemic heart diseases (IHD). The aims of this study were to evaluate serum levels of IL-6, IL-8, TGF-Î² and TNF-Î± in patients with or without CAD, as well as stable angina, and to assess the effects of drug administration on the serum levels of these cytokines. Serum levels of the cytokines were analyzed in the three groups: patients with acute coronary syndrome, stable angina and participants with normal coronary arteries as controls. Cohort study of the patients showed that Nitrocontin was the only drug used in a significantly different pattern between the groups where it was used less frequently in patients with stable angina compared to the acute coronary syndrome or control groups. Serum levels of the evaluated cytokines were not different neither between the studied groups nor between the groups with variable Gensini scores. However, IL-8 in controls that were not engaged in regular exercise was higher than the controls performing regular exercise. In the stable angina group, TNF-Î± in non-smokers was higher than the smokers. It was revealed that serum levels of pro-inflammatory cytokines are not associated with atherosclerosis and stable angina in patients from the South-East of Iran. However, suppressed expression of TGF-Î², may increase the risk of CAD. Exercise can reduce the risk of CAD through downregulation of pro-inflammatory cytokines.